Techno-economic analysis of compressed air energy storage systems - Bozzolani, Emanuele (Cranfield University, 2010)
The continuous escalation of intermittent energy added to the grid and forecasts of peaking power demand increments are rising the effort spent for evaluating the economic feasibility of energy storages. The aim of this research is the techno-economic analysis of Compressed Air Energy Storage (CAES) systems, capable of storing large quantities of off-peak electric energy in the form of high-pressure air, as an ―energy stock‖ which allows the production of high-profit on-peak electricity when required by the grid. Several studies of both conventional and innovative adiabatic concepts are carried out in order to identify and improve the parameters that mostly affect the plant performances. Technical models, that consider the effect of time, are developed to evaluate the parameters that reduce the electric energy spent for compressing the air and that maximize the electric energy produced. In the conventional plant, particular attention is put on the understanding of the effects of air storage pressure range, recuperator, reheating and Turbine Inlet Temperature. For the adiabatic instead, a thorough analysis of the challenging Thermal Energy Storage (TES) is performed for understanding the advantages and drawbacks of this novel efficient concept of CAES. In a further step the economic analyses are aimed at evaluating the different configurations proposed in the technical investigation and the effects that variations of generation train and storage characteristics have on the profitability. After an analysis of the TES impact on the profits, a final comparison is carried out against two existing technologies: Pumped Hydro Energy Storage and gas turbine. The results of these studies confirm, from a technical and economic point of view, the reasons of the growing interest toward CAES as a feasible solution to manage the intermittent energy production. In particular they underline the conventional CAES as promising technology to undertake.
Keywords: CAES; Adiabatic-CAES; Air Storage; Energy Storage; Thermal Energy Storage; Peaking Power Plants